Significance of Asymptomatic Bacteriuria - Jharna Mandal (European Medical Journal, 2017)
Since the recognition of asymptomatic bacteriuria (ABU), several studies have questioned its significance. It is a very common condition, observed in many healthy individuals. Current guidelines mandate that ABU should not be treated in all cases, as it does not seem to improve the outcome. Conditional restrictions for treatment of ABU can be relaxed in certain situations, with minimal exceptions to the rule.